A randomized trial of human C1 inhibitor prophylaxis in children with hereditary angioedema. Issue 5 (29th May 2019) - Aygören‐Pürsün, Emel; Soteres, Daniel F.; Nieto‐Martinez, Sandra A.; Christensen, Jim; Jacobson, Kraig W.; Moldovan, Dumitru; Van Leerberghe, Arthur; Tang, Yongqiang; Lu, Peng; Vardi, Moshe; Schranz, Jennifer; Martinez‐Saguer, Inmaculada
Abstract: Background: Patients with hereditary angioedema with C1 inhibitor deficiency or dysfunction have burdensome recurrent angioedema attacks. The safety, efficacy, and health‐related quality of life (HRQoL) outcomes of C1 inhibitor (C1‐INH) prophylaxis (intravenously administered) in patients aged 6‐11 years were investigated. Methods: Eligible patients were enrolled in a randomized, single‐blind, crossover, phase 3 trial. After a 12‐week baseline observation period (BOP), patients received 500 or 1000 U C1‐INH, twice weekly, for 12 weeks before crossing over to the alternate dose for 12 weeks. The primary efficacy end‐point was the monthly normalized number of angioedema attacks (NNA). HRQoL was assessed using the EuroQoL 5‐dimensional descriptive system youth version and visual analog scale (EQ‐VAS). Results: Twelve randomized patients had a median (range) age of 10.0 (7‐11) years. Mean (SD) percentage reduction in monthly NNA from BOP was 71.1% (27.1%) with 500 U and 84.5% (20.0%) with 1000 U C1‐INH. Mean (SD) within‐patient difference (−0.4 [0.58]) for monthly NNA with both doses was significant ( P = 0.035 [90% CI, −0.706 to −0.102]). Cumulative attack severity, cumulative daily severity, and number of acute attacks treated were reduced. No serious adverse events or discontinuations occurred. Mean EQ‐VAS change from BOP to week 9 of treatment (500 U C1‐INH, 10.4; 1000 U C1‐INH, 21.6) was greater than the minimal important difference, indicating a meaningful HRQoL change. Conclusions: C1‐INH prophylaxis was effective, safe, and well tolerated in children aged 6‐11 years experiencing recurrent angioedema attacks. A post hoc analysis indicated a meaningful improvement in HRQoL with C1‐INH. Trial registration: ClinicalTrials.gov identifier NCT02052141.